The Impact of Unauthorized Guardian Divorce on Shared Property from A Juridical And Sociological Perspective - Zakiyatus Soimah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
This study aims to see the extent of the impact of the breakup of marriage due to unauthorized guardianship on shared property. Using qualitative research and normative juridical approach, this study concluded that as long as the property is obtained during the marriage period, by Law of the Republic of Indonesia Number 1/1974 on Marriage, then automatically the property obtained is joint and divided in two between husband and wife.